고리형 아민과 이산화탄소의 반응에서 온도와 흡수능이 반응열에 미치는 영향 - 최정호(Jeong Ho Choi); 장종탁(Jong Tack Jang); 윤성희(Soung Hee Yun); 조원희(Won Hee Jo); 정진영(Jin Young Jung); 윤여일(Yeo Il Yoon) (한국수소 및 신에너지학회 논문집, 2018)
The effect of temperature and absorption capacity on heat of reaction, which is one of the characteristic studies of $CO_2$ absorption, were investigated in a differential reaction calorimeter (DRC) by using piperazine (PZ) and 2-methylpiperazine (2-MPZ). For all absorbents, $CO_2$ loading capacity decreased with increasing the temperature, while the heat of reaction increased, it figured out that these had a linear correlation between $CO_2$ loading capacity and/or heat of reaction and the temperature. The heat of reaction of all absorbents increased with increasing $CO_2$ loading capacity, especially 2-MPZ rapidly increased at $70^{°}C$. The reason for increase in the heat of reaction was occurred the regeneration of $CO_2$, which is a reverse-reaction, simultaneously with the absorption.